2015
DOI: 10.1242/dev.114850
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction in oocytes of obese mothers: transmission to offspring and reversal by pharmacological endoplasmic reticulum stress inhibitors

Abstract: Over-nutrition in females causes altered fetal growth during pregnancy and permanently programs the metabolism of offspring; however, the temporal and mechanistic origins of these changes, and whether they are reversible, are unknown. We now show that, in obese female mice, cumulus-oocyte complexes exhibit endoplasmic reticulum (ER) stress, high levels of intracellular lipid, spindle abnormalities and reduced PTX3 extracellular matrix protein production. Ovulated oocytes from obese mice contain normal levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
140
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(149 citation statements)
references
References 67 publications
3
140
0
Order By: Relevance
“…Consistent with the previous finding that ER stress activates Bim transcription through CHOP (19), we found that knockdown of CHOP inhibited AUY922-triggered upregulation of Bim. Indeed, chemical chaperones or overexpression of GRP78, which alleviates ER stress (30), attenuated upregulation of CHOP and Bim by AUY922. On the other hand, siRNA inhibition of GRP78 or XBP-1, two wellestablished prosurvival effectors of the UPR (14,15), enhanced upregulation of Bim and apoptosis caused by AUY922.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the previous finding that ER stress activates Bim transcription through CHOP (19), we found that knockdown of CHOP inhibited AUY922-triggered upregulation of Bim. Indeed, chemical chaperones or overexpression of GRP78, which alleviates ER stress (30), attenuated upregulation of CHOP and Bim by AUY922. On the other hand, siRNA inhibition of GRP78 or XBP-1, two wellestablished prosurvival effectors of the UPR (14,15), enhanced upregulation of Bim and apoptosis caused by AUY922.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these changes in substrate utilization occurred in parallel with poor functional outcomes including a greater likelihood of cell arrest (unable to form blastocysts) or smaller blastocysts that had a reduced total cell count. Adding to these findings, isolated oocytes from obese mice had increased mitochondria-derived oxidative stress (33), increased intracellular lipids, and reduced mitochondrial membrane potential (34). Together, these data show that substrate metabolism and mitochondrial function are susceptible to the maternal-fetal environment and may lead to persistent changes in the developing fetal tissue; however, to the best of our knowledge, no studies to date have examined the direct effect of maternal obesity on substrate metabolism in fetal or offspring skeletal muscle.…”
Section: Introductionmentioning
confidence: 89%
“…We (87,88) have previously shown that mitochondrial markers (i.e., MitoTracker and JC-1) are altered in oocytes of obese female mice; thus, we examined whether these changes persist in the developing embryo. Maternal HFD alone increased abundance of Mitotracker staining compared with controls (P Ļ½ 0.01; Fig.…”
Section: Maternal and Paternal Hfd Differentially Alter Mitochondria mentioning
confidence: 99%
“…mtDNA copy number has been previously shown to be reduced in oocytes of obese female mice and to persist into the blastocysts and fetal tissue (88). To investigate whether this occurred in response to paternal or combined dietinduced obesity we examined fetal livers from all diet crosses.…”
Section: Maternal Hfd Impairs Mtdna Copy Number In Fetal Liversmentioning
confidence: 99%
See 1 more Smart Citation